Operationalizing a frailty index using routine blood and urine tests - Ritt, Martin; Jaeger, Jakob; Ritt, Julia Isabel; Sieber, Cornel; Gaßmann, Karl-Günter (Clinical Interventions in Aging, 2017)
Background: Uncomplicated frailty instruments are desirable for use in a busy clinical setting. The aim of this study was to operationalize a frailty index (FI) from routine blood and urine tests, and to evaluate the properties of this FI compared to other frailty instruments.Materials and methods: We conducted a secondary analysis of a prospective cohort study on 306 patients aged >= 65 years hospitalized on geriatric wards. An FI comprising 22 routine blood parameters and one standard urine parameter (FI-Lab), a 50-item FI based on a comprehensive geriatric assessment (FI-CGA), a combined FI (FI-combined [items from the FI-Lab + others from the FI-CGA]), the Clinical Frailty Scale, rule-based frailty definition, and frailty phenotype were operationalized from data obtained during patients' hospital stays (ie, before discharge [baseline examination]). Follow-up data were obtained up to 1 year after the baseline examination.Results: The mean FI-Lab score was 0.34 +/- 15, with an upper limit of 0.74. The FI-Lab was correlated with all the other frailty instruments (all P < 0.001). The FI-Lab revealed an area under the receiver-operating characteristic curve (AUC) for 6-month and 1-year mortality of 0.765 (0.694-0.836) and 0.769 (0.706-0.833), respectively (all P < 0.001). Each 0.01 increment in FI-Lab increased the risk (adjusted for age and sex) for 6-month and 1-year mortality by 7.2% and 7.1%, respectively (all adjusted P < 0.001). When any of the other FIs (except the FI-combined) were also included in the models, each 0.01 increment in FI-Lab score was associated with an increase in the risk of 6-month and 1-year mortality by 4.1%-5.4% (all adjusted P < 0.001).Conclusion: The FI-Lab showed key characteristics of an FI. The FI-Lab can be applied as a single frailty measure or in combination with/ in addition to other frailty instruments.
Keywords: older people; hospital; geriatric wards; frailty; risk stratification; mortality